TRADITIONAL SILVICULTURE AND ITS OPPORTUNITY IN PRIVATELY OWNED FOREST MENOREH MOUNTAIN-KULONPROGO - Priyono Suryanto (Jurnal Kawistara, 2014)
Agroforestry systems (AFS) are emerged to adapt with farmers needs, balancing economic andecological conditions. In recent years, however, there has been shifting from ecology to economy, wheretraditional silviculture emphasizes toward more monoculture with high inputs. This condition willresult in decreasing ecological function of AFS as one of the epitomes of sustainable. This research aimsto know the role of traditional silviculture techniques practiced by farmers and to develop knowledgein AFS management as the basis to compose more productive and sustainable management. Thestudy was conducted in Menoreh mountains, Yogyakarta. There zones based on altitude differenceswere distinguished, namely lowlands (<300 meter above sea level, masl), medium (300-600 masl) andhigh (> 600 masl). Data collecting was done by conducting deep interviews from 46 respondents, whowere chosen randomly in each zone. The data included local knowledge practices, space dynamic andmanagement, traditional silviculture, and orientation of AFS management. The analysis itself was donedescriptively which was integrated through diagnosis approach and design in agroforestry systems.There are there models of AFS management based on there strata of space utilization both in homegardenand dry field, namely initial, intermediate and advanced agroforestry. In the lowland zone is initialagroforestry practicw, characterized by food production orientation. In the middle and upper zone areintermediate and advanced Based on this findings, aproductive and sustainable adaptive silviculture(AS) scheme for AFS management (AS AFS) is required, AS AFS_1 is oriented to keep agroforetybeing able to continualy produce food and its derivatis throughout the management. Intensive spacearrangements and resources sharing silvicuculture measures are important instruments in this model.The second model, AS AFS_2 is for productive intermediate and advanced agroforestry with multilayerproductions. It is suggested in this model to do intensive enrichment planting using tolerant species andcompatible management approach of inter unit lands owned by farmers.